Branding Phenomenon of Local Coffee in Shifting the Existence of Foreign Coffee Brands in Jakarta, Indonesia - Mone, Johana Brigitha; Sari, Eka Wulan; Aras, Muhamad (Unisia, 2022)
Jakarta, the capital city, is home to local coffee brands in Indonesia. As foreign coffee brands emerge in many locations, the branding strategy for local brands requires improvement. This research aims to analyze the branding strategy of local coffee brands regarding their strategy in overcoming the existence of foreign brands in Jakarta. This research used a qualitative approach with a case study method. The research data used open coding, axial coding, and selective coding, and also a reduction process, display, and data verification. The results of the research indicate that a branding strategy is used by a local coffee brand to complement and maintain the existence against foreign coffee brands by creating an impressive value that creates ‘word of mouth’ around the community, using digital media to reach wider consumers, and creating a good brand image to attract consumers.